Współczesne regulacje prawne i perspektywy zmian instytucji japońskiego małżeństwa na kanwie art. 24 Konstytucji Japonii - Jelonek, Barbara (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
About marriage institution was written countless hearings. Marriage is the oldest social institution, which for many years was the foundation of academic discussions and unscientific. Japanese institution of marriage has evolved over the years. Matrimonial law in Japan today is governed by legal acts for example Japanese constitution, Minpō, Koseki and the specific provisions. This article aims to present and explain the legal basis for marriage in Japan, acts directly connecting to this institution and discuss the issue of same-sex marriages in Japan
Keywords: małżeństwo; rozwód; Japonia; konstytucja; LGBT; Minpō (kodeks cywilny); Koseki (rejestr rodzinny)